Using the features of mosaic image and AES cryptosystem to implement an extremely high rate and high secure data hidden: analytical study - Alam, G.M.; Mat Kiah, M.L.; Zaidan, B.B.; Zaidan, A.A.; Alanazi, H.O. (2010)
Mosaic image approaches have been successfully proposed to solve different problems in the image processing such as image segmentation. As it becomes a well known art, there are thousands of mosaic images available in the internet galleries. In addition, there is quite a big number of free mosaic creation software available in the markets. In this paper we will study the features of the mosaic images which can help to implement undetectable data hidden approach (that is steganography approach). Through the research, we found that mosaic image texture is capable to hide up to five LSB layers. Furthermore, there are several papers stated clearly "secure steganography application should be engaged with cryptography". Thus, AES/Rijndael algorithm has been proposed together with the five LSB steganography to ensure the highest rate of data hidden side by side with high level of security. The evaluation of steganography approaches required either objective test (that is passing the SNR, PSNR, MSE or RMSE exam) or subjective test (that is using survey). Many researches conducted to approve the failure of the objective exam. Therefore, we evaluated our approach using the subjective test. Our survey shown the approximate of 99 is the success rate for the mosaic cover, comparing with approximately 50 the success of normal images. Â© 2010 Academic Journals.